Brain-derived neurotrophic factor in the cerebrospinal fluid increases during electroconvulsive therapy in patients with depression: a preliminary report - Mindt, Sonani; Neumaier, Michael; Hellweg, Rainer; Sartorius, Alexander; Kranaster, Laura (The journal of ECT, 2020)
Objective  - Preclinical evidence suggests a role for brain-derived neurotrophic factor (BDNF) in the mode of action of electroconvulsive therapy (ECT). Clinical data regarding BDNF levels in serum or plasma are more inconsistent. We measured BDNF levels from the cerebrospinal fluid (CSF) in patients with major depression before and shortly after a course of ECT. - Methods  - Cerebrospinal fluid and serum BDNF levels were determined using commercially available enzyme-linked immunosorbent assay (ELISA) kits. - Results  - We included 9 patients with a severe depressive episode within a major depressive disorder into the study. The CSF BDNF concentrations at baseline were lower compared with those CSF BDNF levels after the complete ECT treatment (P = 0.042), whereas no such a constellation was found for serum BDNF. No associations between the BDNF levels and the amount of individual ECT sessions or the reduction of the depressive symptoms were found. - Conclusions  - For the first time, it has been shown that CSF BDNF concentrations increase during a course of ECT in patients with a severe unipolar depressive episode, which is in line with the neurotrophin hypothesis as a mode of action of ECT, although it was not possible to demonstrate either a dose-effect relation or a relationship with the actual antidepressant effects in our small sample. Major limitation is the small sample size.